(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
In this paper, we propose the development of a Gas Leakage Detection System utilizing Arduino microcontroller technology and a GSM module for real-time alerting. The system aims to enhance safety measures by promptly identifying and notifying users about the presence of potentially hazardous gas concentrations. The core components include an Arduino board, a Gas sensor module (MQ series), and a GSM module (SIM900). The gas sensor continuously monitors the ambient air for gas concentrations, and when levels surpass a predefined threshold, an alarm is triggered. Simultaneously, the system utilizes the GSM module to send an alert via SMS to predefined mobile numbers, providing instant notifications to relevant stakeholders.